2015
DOI: 10.1111/area.12180
|View full text |Cite
|
Sign up to set email alerts
|

A channel evolution model to guide sustainable urban stream restoration

Abstract: Channel evolution models (CEMs) are used to structure the interpretation of observed channel morphology to support long-term restoration of these systems. However, channels reflect the variety of their watersheds' climatological, ecological and physiographic contexts, and so no single CEM can be truly 'global' . Unrecognised differences between the assumptions and the reality of evolutionary trajectories of particular streams can subsequently lead to restoration actions that neither fully achieve their intende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(38 citation statements)
references
References 52 publications
4
34
0
Order By: Relevance
“…For example, the lower reach of Wilket Creek has an enlargement ratio (E r ) of 2.6 in comparison with the 1958 channel (Figure 8), which is within the expected range for temperate streams (Chin, 2006). The significant increase in depth (0.4-0.5 m or~75%) is also in line with expectations from other studies (Chin, 2006), and together with the exposure of till in lower parts of the the channel banks confirms that the geology is not acting to create overly widened channels, as would be the case for a bedrock channel (Booth and Fischenich, 2015), and that the channel can in fact incise into the bed material and till. Over 200 mm of rain fell on saturated ground over a 48-hour period in this storm, and damage in the larger Don River catchment was well documented, with a number of bridges failing and considerable damage to buildings in the floodplain.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…For example, the lower reach of Wilket Creek has an enlargement ratio (E r ) of 2.6 in comparison with the 1958 channel (Figure 8), which is within the expected range for temperate streams (Chin, 2006). The significant increase in depth (0.4-0.5 m or~75%) is also in line with expectations from other studies (Chin, 2006), and together with the exposure of till in lower parts of the the channel banks confirms that the geology is not acting to create overly widened channels, as would be the case for a bedrock channel (Booth and Fischenich, 2015), and that the channel can in fact incise into the bed material and till. Over 200 mm of rain fell on saturated ground over a 48-hour period in this storm, and damage in the larger Don River catchment was well documented, with a number of bridges failing and considerable damage to buildings in the floodplain.…”
Section: Discussionsupporting
confidence: 89%
“…In contrast with the classic concave profile of a graded channel (Mackin, 1948;Schumm and Lichty, 1965), many channel profiles in the region are convex or 's' shaped (Vocal Ferencevic and Ashmore, 2012;Thayer et al, 2016) as channels continue to rework the lag material from relatively recent glacial melt channels (Church and Slaymaker, 1989;Newbury, 2013;Phillips and Desloges, 2015). The model builds on previous work (Schumm et al, 1984;Simon, 1989;Hawley et al, 2012;Booth and Fischenich, 2015), but also includes the observed dynamics of particle size, till exposure, and planform adjustments in Wilket Creek. The current study thus provides a test case of enlargement and evolution in a channel with a resistant bed.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Additional complex responses to channel instability include tributary rejuvenation through headcutting, accelerated rates of lateral mobility in meandering rivers [13,14] and channel widening as flow is deflected around maturing sediment bars, both of which could threaten linear flood defences not set back from the channel. While Lane's relationship provides a useful concept to describe the capability of an alluvial stream to adjust its morphology through sediment erosion, transport and deposition processes [15] and has provided a platform to develop more rigorous models of qualifying (e.g., [16]) and quantifying (e.g., [6]) river channel change and framing river restoration methods (e.g., [17,18]), critically it does not state explicitly how channel geometry and/or planform might change, or whether the bed and/or banks are likely to adjust in response to a given sediment imbalance scenario. Also, in some cases, the channel boundary might not be free to adjust or might be responding to other influences not accounted for in the relationship [19] and therefore, despite efforts to extend the relationship to include morphological variables [20][21][22], Lane's approach remains a qualitative, 'indicative' treatment of potential channel instability (degradation vs aggradation) that is not necessarily a reliable predictor of the 'type' of morphological response, e.g., bed scour, bank erosion, bar formation or some combination thereof.…”
Section: Introductionmentioning
confidence: 99%